Predictive value of synaptic plasticity for functional decline in patients with multiple sclerosis - Balloff, Carolin; Janßen, Lisa Kathleen; Hartmann, Christian Johannes; Meuth, Sven Günther; Schnitzler, Alfons; Penner, Iris-Katharina; Albrecht, Philipp (Frontiers in Neurology, 2024)
Background Previous research suggested that quadripulse (QPS)-induced synaptic plasticity is associated with both cognitive and motor function in patients with multiple sclerosis (MS) and does not appear to be reduced compared to healthy controls (HCs). Objective This study aimed to explore the relationship between the degree of QPS-induced plasticity and clinically significant decline in motor and cognitive functions over time. We hypothesized that MS patients experiencing functional decline would exhibit lower levels of baseline plasticity compared to those without decline. Methods QPS-induced plasticity was evaluated in 80 MS patients (56 with relapsing-remitting MS and 24 with progressive MS), and 69 age-, sex-, and education-matched HCs. Cognitive and motor functions, as well as overall disability status were evaluated annually over a median follow-up period of 2 years. Clinically meaningful change thresholds were predefined for each outcome measure. Linear mixed-effects models, Cox proportional hazard models, logistic regression, and receiver-operating characteristic analysis were applied to analyse the relationship between baseline plasticity and clinical progression in the symbol digit modalities test, brief visuospatial memory test revised (BVMT-R), nine-hole peg test (NHPT), timed 25-foot walk test, and expanded disability status scale. Results Overall, the patient cohort showed no clinically relevant change in any functional outcome over time. Variability in performance was observed across time points in both patients and HCs. MS patients who experienced clinically relevant decline in manual dexterity and/or visuospatial learning and memory had significantly lower levels of synaptic plasticity at baseline compared to those without such decline (NHPT: β = −0.25, p = 0.02; BVMT-R: β = −0.50, p = 0.005). Receiver-operating characteristic analysis underscored the predictive utility of baseline synaptic plasticity in discerning between patients experiencing functional decline and those maintaining stability only for visuospatial learning and memory (area under the curve = 0.85). Conclusion Our study suggests that QPS-induced plasticity could be linked to clinically relevant functional decline in patients with MS. However, to solidify these findings, longer follow-up periods are warranted, especially in cohorts with higher prevalences of functional decline. Additionally, the variability in cognitive performance in both patients with MS and HCs underscores the importance of conducting further research on reliable change based on neuropsychological tests.